2014
DOI: 10.1016/j.nedt.2013.06.009
|View full text |Cite
|
Sign up to set email alerts
|

End of life care education, past and present: A review of the literature

Abstract: This review highlights issues with end of life care education and suggests that end of life care simulation is an innovative strategy that may help to prepare undergraduate nursing students to provide quality end of life care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
118
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 30 publications
5
118
0
4
Order By: Relevance
“…Studies whose subjects are Nursing students have shown that dealing with death and dying generates anxiety 9 , and the professionals feel unprepared to provide care for terminal patients [12][13] . In view of this, the question is: how do Medicine students deal with situations that involve death?…”
Section: Comunicação Saúde Educaçãomentioning
confidence: 99%
See 1 more Smart Citation
“…Studies whose subjects are Nursing students have shown that dealing with death and dying generates anxiety 9 , and the professionals feel unprepared to provide care for terminal patients [12][13] . In view of this, the question is: how do Medicine students deal with situations that involve death?…”
Section: Comunicação Saúde Educaçãomentioning
confidence: 99%
“…Furthermore, it is possible to verify the absence of didactic books and contents about death in the curricula [10][11]13,17 . The school experiences the denial of death and transports it to teaching 13,17 .…”
Section: Death Evokes Unpleasant Feelings and Sensationsmentioning
confidence: 99%
“…A previous study reported that negative attitudes from nurses, such as the feeling of fear and anxiety in nursing care, could decrease the quality of care in dying patients (Grubb & Arthur, 2016). Furthermore, another previous study also reported that negative responses of nurses facing a dying process were evoked such as anxieties, fears, and the helplessness that influence the quality of care (Gillan, van der Riet, Jeong, Riet, & Jeong, 2014). Beck, Tornquist, Brostrom, and Edberg (2012) stated that nurses need to describe their feeling through pained expression when caring for the dying patients.…”
mentioning
confidence: 99%
“…However, recent studies reported that nursing students feel unprepared when they should face patients and family within dying care (Gillan et al, 2014;Wallace et al, 2009). Grubb and Arthur (2016) emphasized that positive students' attitudes in caring for dying patients can be used as an indicator of effective therapeutic relationship with dying patients.…”
mentioning
confidence: 99%
“…Unfortunately, studies on nurses' attitudes to caring for terminally ill persons showed that dealing with death and dying evokes negative emotions, such as feelings of helplessness or surrender, and creates fears, anxieties and anguishes that affect the quality of the care provided to patients [3][4][5] . A recent study reported that nurse assistants often described palliative care as a contrast to the everyday care they performed, in that they had a concrete possibility to provide the care the patient's needed [6] .…”
mentioning
confidence: 99%